PERUSAHAAN MANUFAKTUR SUB-SEKTOR OTOMOTIF DAN KOMPONEN DI BURSA EFEK INDONESIA - Putri, Cintamy Prananti (Jurnal Akuntansi AKUNESA, 2013)
This research was conducted to examine the effect of variables Net Profit Margin (NPM), Earning per Share (EPS), Return on Assets (ROA) and Return on Equity (ROE) of Firm Value (PBV) on the Indonesian automotive allied products companies listed on the Stock Exchange the period 2010-2012. Quantitative data for this study get from Indonesia Stock Exchange. The data were analyzed by linear regression analysis using SPSS version 16.0. Analysis technique used is multiple regression analysis. Hypothesis testing is performed with simultaneous F test and partial t test, with a significance level of 5%.The result of this count, NPM and ROA have positive and significant influence to firm value (PBV), while EPS and ROE variable have negative and significant influence to firm value (PBV) of automotive and allied products companies. Key words: Net Profit Margin (NPM), Earning per Share (EPS), Return on Assets(ROA), Return on Equity (ROE), Firm Value